Obsessive-Compulsive Symptoms as a Manifestation of Homocystinuria - Vera Froes; Hugo Afonso; Zita Gameiro (Case Reports in Psychiatry)
Homocystinuria is a rare autosomal recessive metabolic disorder due to a defect in the cystathionine β-synthase (CBS) that leads to high homocysteine plasma levels. Psychiatric symptoms secondary to homocystinuria have been described in the literature; however, there is a lack of information about obsessive-compulsive symptoms correlated to this disorder. We describe the case of a 39 years old man, diagnosed with homocystinuria in childhood, with no previous psychiatric history that presented obsessive-compulsive disorder (OCD) like symptoms, as a manifestation of homocystinuria. This case underlines the importance for a psychiatrist to explore medical nonpsychiatric history, especially when presentation is abrupt, atypical, or in treatment-resistant cases.